Dificuldades e desafios dos gestores em unidade de atenção básica no município de Santos - Matos, Renato Aparecido Dutra [UNIFESP] (2020)
In view of the conjuncture of political and economic crisis that has been affecting the country, Health Services in Primary Care are increasingly being discussed in terms of Health Management, quality of care provided, access and qualified listening , solving identified problems and resolving referrals. In this study, the qualitative approach was chosen through an individual structured interview with the Primary Health Care Unit Managers in the municipality of Santos. It aims to analyze the perception of Primary Health Care Unit Managers in the Municipality of Santos regarding the difficulties and challenges of being a Manager to ensure universal, comprehensive and equal access in the Unified Health System. The current service scenario in Primary Care, it has had repercussions on managers in the way teams are organized, service flows and access to users. The qualitative dimension of this study contributed to understand about the difficulties and challenges of the Manager in the Primary Care Unit in the Municipality of Santos, despite the limitations, the Managers are able to conduct necessary strategies for public, universal, integral and equitable health, which sometimes cannot perceived by the managers themselves as determinants of their actions.